2018
DOI: 10.1186/s12941-018-0282-9
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes-purpura fulminans as an invasive form of group A streptococcal infection

Abstract: BackgroundStreptococcus pyogenes is an uncommon pathogen of purpura fulminans, and the pathogenesis of S. pyogenes-purpura fulminans remains unclear because of paucity of cases. We reported a pediatric case of S. pyogenes-purpura fulminans with literature review of the disease.Case presentationA 3-year-old boy showed limping, lethargy and acral gangrene within 24 h. A diagnosis of S. pyogenes-purpura fulminans was made for bacterial isolation from throat and peripheral blood. Intensive therapy led to a surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(23 reference statements)
1
12
0
2
Order By: Relevance
“…As hypo brinogenemia is frequently related to the bleeding tendency in hematological diseases patient with DIC and organ failure is often associated with infectious disease patient with DIC, hypo brinogenemia is considered to be frequently associated with DIC in patients with hematological diseases but rarely with DIC in patients with infectious disease [5,14]. However, some septic cases have been reported to be associated with severe bleeding [23,24]. Our analysis of the PMS data revealed that hypo brinogenemia was present in 10.3% of infectious diseases with DIC and suspected DIC, suggesting that hypo brinogenemia is sometimes associated with infectious-type DIC.…”
Section: Discussionmentioning
confidence: 99%
“…As hypo brinogenemia is frequently related to the bleeding tendency in hematological diseases patient with DIC and organ failure is often associated with infectious disease patient with DIC, hypo brinogenemia is considered to be frequently associated with DIC in patients with hematological diseases but rarely with DIC in patients with infectious disease [5,14]. However, some septic cases have been reported to be associated with severe bleeding [23,24]. Our analysis of the PMS data revealed that hypo brinogenemia was present in 10.3% of infectious diseases with DIC and suspected DIC, suggesting that hypo brinogenemia is sometimes associated with infectious-type DIC.…”
Section: Discussionmentioning
confidence: 99%
“…The final common pathway in the pathogenesis of all the subtypes is deficiency and/or inactivation of protein C, which hampers anticoagulation. 1 Idiopathic PF occurs secondary to formation of transient autoantibodies against proteins C and S. This process starts 7 to 10 days after the onset of varicella or streptococcal infections. 2 Neonatal PF is characterized by rapid onset within 72 hours of birth and constitutes cerebral hemorrhage, purpuric skin lesions, and acral gangrene resulting from a heritable deficiency of protein C. 3 AIPF is the most common subtype, occurs superimposed on sepsis, and is associated with the thrombotic subtype of disseminated intravascular coagulation (DIC).…”
Section: Introductionmentioning
confidence: 99%
“…Purpura fulminans (PF) is classified into three subtypes, idiopathic PF, neonatal PF and acute infectious PF (AIPF). The final common pathway in the pathogenesis of all the subtypes is deficiency and/or inactivation of protein C, which hampers anticoagulation 1 . Idiopathic PF occurs secondary to formation of transient autoantibodies against proteins C and S. This process starts 7 to 10 days after the onset of varicella or streptococcal infections 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is an unusual and dramatic skin manifestation of disseminated intravascular coagulation [7][8][9]. Macroscopically, PF usually starts with well-demarcated macules which rapidly develop central hemorrhagic necrosis and progress to retiform purpura, sometimes with hemorrhagic vesicles or bulla resulting in gangrene [10][11][12]. In the presence of septic shock, purpura fulminans usually affects the extremities because of poor blood perfusion to distal parts of the body [13].…”
Section: Introductionmentioning
confidence: 99%
“…PF is classified into 3 categories: neonatal PF (due to an autosomal-dominant inherited protein C deficiency), acute infectious PF, and idiopathic PF (usually post-infectious due to transient acquired protein S and/or S deficiency or secondary to medications). The most common form of PF is acute infectious PF, most commonly associated with encapsulated bacterial pathogens (such as Neisseria meningitides, S. pneumoniae, Haemophilus influenza), among others [11][12][13].…”
Section: Introductionmentioning
confidence: 99%